MANAJEMEN BERBASIS SEKOLAH (MBS) PADA SMA KRISTEN KALAM KUDUS PEKANBARU (STUDI KASUS KUALITAS PENDIDIK) - ", Risty; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
School-Based Management is a situation where the government gives autonomy to theschools, so that schools have the authority to manage and improve the quality of theresources in a better quality education, as well as aiming to improve the efficiency, quality,and educational equity. Increased efficiency, among others, flexibility is obtained throughresource management community participation. While quality improvement can be obtainedmemalui terhadao parent participation school, school and classroom management flexibility,increased professionalism of teachers and principals, curriculum development andimprovement and systems of evaluation, improvement of educational facilities, developmentand procurement of teaching materials, and training for teachers and education personnelother. While equity is obtained through public participation peningatan that allows thegovernment to concentrate on a particular group. But in fact there are teachers who do nothave qualifications as educators in general. Study of phenomena, the formulation of theproblem of this research is how the implementation of school-based management in theKristen Kalam Kudus High School Word of Pekanbaru and the factors that influence thesuccess of MBS at a Kristen Kalam Kudus high school Pekanbaru.This study used a descriptive analysis method. Data collection technique is theobservation, interviews, and library research. Key informants of this study is the high schoolprincipal Kristen Kalam Kudus Pekanbaru. In the School Based Management (MBS) KristenKalam Kudus High School In Pekanbaru.The results showed that not maximal application of school-based management isapplied by the Kristen Kalam Kudus High School Pekanbaru. In connection with positionsand professions can be seen that there are still teachers who do not have fully qualified as aeducator.Serta not optimal implementation factors that influence school-based management,which is still low government support for private schools in the development and welfare ofteachers.Key words: School-Based Management, Administration, Management